Productivity and efficiency analysis in presence of pollution: a review of non-parametric methods. (1st January 2013) - Manello, Alessandro
During the past 20 years, a rising interest in environmental protection and in the sustainability of production processes has stimulated scientific research to create indicators of efficiency and productivity that is able to consider undesirable outputs. The number of papers written is impressive, as well as the number of proposed techniques. The researchers and practitioners face great difficulties in piecing together contributions from different fields. This review is aimed at drawing a detailed 'state of the art' of non-parametric methods used to measure environmental and economical efficiency, showing the main features of each tool. Many recent papers are analysed and classified on the basis of some simple categories, to advise the readers in the most appropriate methodological choice. Moreover, one of the most frequently applied tools in recent empirical works, the directional distance function model (DDF) is discussed at length and an exhaustive collection of papers adopting DDF is proposed as a conclusive remark. Finally, a general overview of the main advantages and limits for each method systematises previous findings and concludes this survey.